Taking stock of firm-level and country-level benefits from foreign direct investment. Issue 2 (27th June 2018) - Bruno, Randolph L.; Campos, Nauro F.; Estrin, Saul
Abstract : Purpose: This paper aims to conduct a systematic meta-analysis on emerging economies to summarize these effects and throw light on the strength and heterogeneity of these conditionalities. Design/methodology/approach: This paper proposes a new methodological framework that allows country- and firm-level effects to be combined. The authors hand collected information from 175 studies and around 1, 100 estimates in Eastern Europe, Asia, Latin America and Africa from 1940 to 2008. Findings: The two main findings indicate that "macro" effects are much larger than enterprise-level ones, by a factor of at least six and the benefits from foreign direct investment (FDI) into emerging economies are substantially less "conditional" than commonly thought. Originality/value: The empirical literature has not reached a conclusion as to whether FDI yields spillovers when the host economies are emerging. Instead, the results are often viewed as conditional. For macro studies, this means that the existence and scale of spillover effects are contingent on the levels of institutional, financial or human capital development attained by the host economies. For enterprise-level studies, conditionality relates to the type of inter-firm linkages, namely, forwards, backwards or horizontal.